2004
DOI: 10.1590/s1415-43662004000200026
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição espacial de pivôs centrais no Brasil: I - região sudeste

Abstract: Resumo:Resumo: Resumo: Resumo: Resumo: Quando se buscam, em literatura, dados sobre a irrigação no Brasil, o que se encontra disponível é a área irrigada por estado e por método de irrigação. A distribuição dentro dos estados, o número de equipamentos e seu tamanho são de difícil obtenção, mesmo junto às indústrias. No entanto, essas são informações fundamentais quando se pretende estudar a disponibilidade hídrica ou o potencial de crescimento da área irrigada de uma região, por exemplo, temas esses bastante a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
1
4
0
7
Order By: Relevance
“…Comparing these data with those estimated by SCHMIDT et al (2004), one notices an increase of approximately 52% in the number of devices. Relating also the area occupied by these equipments during the study period with the estimation made by CHRISTOFIDIS (2008), it is observed an increase of almost three times in the area irrigated by center pivots.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Comparing these data with those estimated by SCHMIDT et al (2004), one notices an increase of approximately 52% in the number of devices. Relating also the area occupied by these equipments during the study period with the estimation made by CHRISTOFIDIS (2008), it is observed an increase of almost three times in the area irrigated by center pivots.…”
Section: Resultssupporting
confidence: 60%
“…According to SCHMIDT et al (2004), the margin of error related to counting the number of pivots when using satellite images is not higher than 5%, but it is influenced by image resolution, size of the pivot, cloudiness, image overlapping and the lack of contrast between the occupation and the neighboring soil. Given this margin of error, the total number of pivots in the state of Minas Gerais would vary between 3682 and 4060 units.…”
Section: Resultsmentioning
confidence: 99%
“…Diante deste fato, com a crescente demanda hídrica e, por outro lado, a deterioração dos recursos naturais e sua escassez em algumas regiões especialmente no semiárido Brasileiro o gerenciamento integrado dos recursos hídricos torna-se cada vez mais imprescindíveis (SCHMIDT et al, 2004).…”
Section: Introductionunclassified
“…A discriminação visual destas áreas, que apresentam forma predominantemente circular, é relativamente fácil, principalmente quando existe um contraste de uso e cobertura com o entorno. Schmidt et al (2004) A partir de 2003 os produtos do satélite sino-brasileiro para recursos terrestres (CBERS) passaram a ser disponibilizados gratuitamente, tornando-se mais uma opção de dados para estudos relacionados à identificação de áreas agrícolas no Brasil. O sensor CCD, do satélite CBERS-2B (CCD/CBERS-2B), fornece imagens de uma faixa de 113 km de largura no terreno, com resolução espacial de 20 m e resolução temporal de 26 dias.…”
Section: Introductionunclassified